2006
DOI: 10.4269/ajtmh.2006.75.139
|View full text |Cite
|
Sign up to set email alerts
|

EFFICACY AND SAFETY OF Β-Arteether AND Α/Β-Arteether FOR TREATMENT OF ACUTE PLASMODIUM FALCIPARUM MALARIA

Abstract: One hundred thirty-eight adult patients with acute Plasmodium falciparum malaria were randomized to receive either beta-arteether or alpha/beta-arteether. The drugs were administered in the dose of 150 mg once a day intramuscularly for three consecutive days in hospitalized patients. After one week of hospitalization, patients were followed-up for three weeks after release from the hospital. There was no statistically significant difference between cure rates, mean fever clearance time (FCT), mean parasite cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…The novel endo-peroxide link is essential for the antimalarial activity. Artemether (N2) and arteether (N3) are the most well-studied analogs among many synthetic derivatives and are used in malaria-prone regions, particularly India (131). Artemether and sodium artesunate (a hemisuccinate derivative of dihydroartemisinin) (N4) have been added by the World Health Organization to its Model List of Essential Medicines (132).…”
Section: Artemisia Annua (Qinghao Artemisinin Derivatives)mentioning
confidence: 99%
“…The novel endo-peroxide link is essential for the antimalarial activity. Artemether (N2) and arteether (N3) are the most well-studied analogs among many synthetic derivatives and are used in malaria-prone regions, particularly India (131). Artemether and sodium artesunate (a hemisuccinate derivative of dihydroartemisinin) (N4) have been added by the World Health Organization to its Model List of Essential Medicines (132).…”
Section: Artemisia Annua (Qinghao Artemisinin Derivatives)mentioning
confidence: 99%
“…The synthetic derivatives artemether (P2) and arteether (P3) are widely used in malaria-prone regions, particularly India [156], and the World Health Organization lists artemether and sodium artesunate (a hemisuccinate derivative of dihydroartemisinin) (P4) in its Model List of Essential Medicines [157].…”
Section: Antimalarial Compoundsmentioning
confidence: 99%
“…It has passed clinical trials for safety and has been found to be efficacious against the asexual stages of P. falciparum [57]. Gametocytocidal activity has been demonstrated against P. cynomolgi B [56,58] at a single dose of 10 mg/kg.…”
Section: Gametocytocidal Therapies Under Developmentmentioning
confidence: 99%